Chemical control of species of genus Commelina - Rúbia de Moura Carneiro; Gabriela de Souza da Silva; Francisco Freire de Oliveira Junior; Fernando Ramos de Souza; Luana Jessica da Silva Ferreira; Ana Claudia Langaro; Camila Ferreira de Pinho (Revista Ciência Agronômica)
ABSTRACT The aim of this study was to evaluate control of the species Commelina benghalensis and Commelina diffusa using post-emergent herbicides applied alone and in mixture. Two replicated experiments (EI and EII) were conducted to evaluate two species of Commelina, with four to six leaves (EI) and six to ten leaves (EII). The experiments included 27 treatments with the following post-emergent herbicides that were applied alone or in mixture: glyphosate; 2,4-D; triclopyr; dicamba; carfentrazone; saflufenacil; flumioxazine; chlorimuron; cloransulam and diclosulam+halauxifen. Plant control and the transient fluorescence of chlorophyll-a were visually analysed 21 and 42 days after application (DAA). At 42 DAA, plants were collected to determine the shoot dry weight. The data were submitted to ANOVA (p ≤ 0.05) and compared using the Scott-Knott test. The triple mixtures were effective in controlling both species. The triple mixtures that included carfentrazone afforded faster effective control compared to mixtures containing saflufenacil and flumioxazine. Triclopyr gave faster control of both species compared to the other auxinic herbicides. Both species respond differently to auxinic herbicides, and are more difficult to control when they have between six and ten leaves.